2010
DOI: 10.1111/j.1365-3024.2009.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipoproteins in visceral leishmaniasis and their effect onLeishmania-infected macrophages

Abstract: This work aimed at investigating the lipid profile of zoonotic visceral leishmaniasis (VL) patients' sera and the effect of lipoproteins on the in vitro production of tumour necrosis factor-alpha (TNF-alpha), interleukin (IL)-6, IL-10 and IL-12 by Leishmania infantum-infected and uninfected macrophages. Lipids were quantified in 26 VL patients' sera and 26 healthy controls from a VL endemic area. The patients' sera had higher triglyceride and very low density lipoprotein (VLDL) levels, and much lower apolipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 58 publications
3
32
0
10
Order By: Relevance
“…The HDL levels (reference values >35mg/dl) and triglycerides levels (reference value <150mg/dL) were below and higher than normal in patients before treatment, respectively. These results are in agreement with Soares et al 25 , who showed that patients with VL had high triglycerides levels and low HDL, LDL and total cholesterol levels. Other studies of visceral leishmaniasis and other infectious diseases, such as HIV and schistosomiasis, have reported the same lipid changes 28,[51][52][53][54] .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The HDL levels (reference values >35mg/dl) and triglycerides levels (reference value <150mg/dL) were below and higher than normal in patients before treatment, respectively. These results are in agreement with Soares et al 25 , who showed that patients with VL had high triglycerides levels and low HDL, LDL and total cholesterol levels. Other studies of visceral leishmaniasis and other infectious diseases, such as HIV and schistosomiasis, have reported the same lipid changes 28,[51][52][53][54] .…”
Section: Discussionsupporting
confidence: 83%
“…Low cholesterol levels in humans decrease the number of circulating lymphocytes, thus increasing the chances of mortality 23,34 . The decrease in lipoproteins may affect the immune response and the pathogenesis of the disease, as lipoproteins are related to the production of TNF-α, IL-6 and IL-10 25 . In addition to being targets for the immunomodulatory activity of lipoproteins, macrophages express lipoprotein receptors and are the host cells of the Leishmania parasite 57 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism controlling its production is poorly understood and its acquirement by tissues is dependent upon the activity of enzymes such as endothelial lipoprotein lipase, which may be impaired in patients with VL [33]. Another study on plasma lipoproteins and its effect on Leishmania infected macrophages in VL suggests that LDL influence the production of tumor necrosis factor (TNF-α), while VLDL stimulates only the production of interleukin-10 (IL-10) and perhaps increase the permissiveness of macrophage to leishmania growth [34].…”
Section: Discussionmentioning
confidence: 99%